PENGARUH MEDIA PEMBELAJARAN ZEP QUIZ BERBASIS PROBLEM BASED LEARNING TERHADAP PEMAHAMAN MATERI BUDAYA TAAT HUKUM (Penelitian Quasi Eksperimen di Kelas X SMA Pasundan 8 Bandung) - Raisha Nadya Maharani; Cahyono; Delila Kania (KAMPUS AKADEMIK PUBLISING, 2026)
This study examined the significant effect of Zep Quiz learning media integrated with Problem Based Learning on Grade X students’ understanding of law-abiding culture material at SMA Pasundan 8 Bandung. A quantitative quasi-experimental method with a nonequivalent control group pretest-posttest design was employed. The sample consisted of 58 students: 29 students in class X.4 as the experimental group and 29 students in class X.5 as the control group. Data were collected using a conceptual-understanding test and analyzed with descriptive statistics, a homogeneity test, and an independent-samples t-test using IBM SPSS 25. The experimental group’s mean score increased from 78.45 to 88.79, while the control group’s mean score increased from 76.90 to 87.41. The homogeneity test yielded a significance value of 0.203, and the hypothesis test reported a two-tailed significance value of 0.047. Therefore, the study concluded that Zep Quiz-based Problem Based Learning had a significant effect on students’ understanding of law-abiding culture material.